Genus Cosmarium Corda from Thrissur Kole lands, Kerala - Tessy Paul, P; Sreekumar, R. (Recent Research in Science and Technology, 2015)
The present investigation deals with sixty eight taxa of Cosmarium Corda collected from the Kole lands of Thrissur, Kerala. The Kole lands constitute part of Vembanad-Kol, which is declared as one of the Ramsar sites of Kerala. All the taxa are systematically described with illustrations and their distribution in India. Of these, six taxa are first time reported from India and twenty nine taxa are new additions to the algal flora of Kerala. C. geminatum Lund. var. ornatum Behre, C. indentatum Gronbl. var. ellipticum Scott & Gronbl., C. pseudoconnatum Nordst. var. constictum West, C. quadrifarium Lund., C. quadriverrucosum West & West var. undulatum Scott & Prescott and C. subturgidum (Turn.) Schmidle are the new additions to the desmid flora of India.